Development of Mechanical Puzzles as Learning Media for Operation Counting Addition for Hearing Impaired Children (EDUTECH, 2022)
: Learning mathematics requires media as a bridge in mastering mathematical concepts because it is not easy to understand and abstract so that interactive learning media are needed to make children not only learn theoretically but also learn practically, including for children with hearing impairments. Children with hearing impairments have problems in acquiring vocabulary and have difficulty processing information, one of which is in learning addition arithmetic operations so that concrete media that involves physical activity to make it easier for students to learn mathematics is needed . Based on that, the researcher aims is to conduct research on the development of mechanical puzzle media as a learning medium for addition operations in the form of concrete objects for students with hearing impairments. The research model used in this study is the development of learning tools with a 4-D development model consisting of 4 main stages, namely Define , Design , Develop and Disseminate with the test subject of 5 students.with hearing impairment class 1 in SLB Karnnamanohara. Data collection techniques used are interview and questionnaire techniques with data collection stages in the form of interviews with teachers and expert validation. The media expert validation assessment showed that the media expert validation percentage was 87.5% (very feasible) and material expert was 79% (very feasible). These results indicate that in the mechanical puzzle overall very feasible to use with some suggestions for further improvement on the indicators of mathematical concepts and graphic design.